Equilibrium and non-equilibrium freezing of water in clay-water systems - Kozłowski, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The temperature of spontaneous nucleation Tsn and the equilibrium freezing point Tf were determined for six monomineral, homoionic clayey soils by use of the Differential Scanning Calorimetry (DSC) technique. The temperature of spontaneous nucleation Tsn was determined on the cooling run, as the initial temperature of the observed exothermic peak. The temperature of equilibrium freezing (or melting) Tf was comprehended as the initial temperature of the last non-zero thermal impulse in the diagram of real thermal impulses distribution q(T) obtained on warming.The supercooling was calculated as the difference between Tf and Tsn.
Keywords: system glina-woda; kalorymetr skaningowy; zamarzanie; temperatura krystalizacji; clay-water systems; scanning calorimetry; temperature of spontaneous nucleation; freezing